Sport tourism management in Poland and Slovakia: Olympic Games as an opportunity and a shared vision, the potential of joint promotion - Dominik Borek; Jozef Polačko (Journal of Education, Health and Sport, 2023)
This article focuses on the promotional aspects related to the tourist attractiveness of the neighboring countries-Poland and Slovakia. The purpose of the article is to analyze the issue in question and point out the importance of the search for ways to increase the effectiveness of management of the area of tourism promotion in both countries. The authors used an empirical research method with quantitative-statistical and qualitative studies on specific promotional campaigns. The Olympic Games have the greatest marketing potential among sporting events, as the most important sporting event in the world. The possibility of organizing such an event in Poland and Slovakia would certainly serve to improve the recognition rates of both countries. The authors will try to demonstrate this potential as part of the considerations in this article. Acknowledgement: This paper was supported by the project NP-KSV-ET-01-2023-12/ST - International cooperation in the field of development, management and law in tourism and sports between the Republic of Poland and Slovak Republic. The views expressed in this paper are those of the authors and should not be taken as reflecting the position of any authority, entity or institution. This article presents the legal status as of 25 March 2023.